2020
DOI: 10.3390/cells9010134
|View full text |Cite
|
Sign up to set email alerts
|

HIF1α/TET1 Pathway Mediates Hypoxia-Induced Adipocytokine Promoter Hypomethylation in Human Adipocytes

Abstract: Obesity is associated with the accumulation of dysfunctional adipose tissue that secretes several pro-inflammatory cytokines (adipocytokines). Recent studies have presented evidence that adipose tissues in obese individuals and animal models are hypoxic, which may result in upregulation and stabilization of the hypoxia inducible factor HIF1α. Epigenetic mechanisms such as DNA methylation enable the body to respond to microenvironmental changes such as hypoxia and may represent a mechanistic link between obesit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…A mechanistic role of inflammasome activation in determining aerobic capacity (measured by peak oxygen uptake) was suggested since the percentage of methylation of the ASC gene and plasma IL-1β levels correlated with aerobic capacity in stable outpatients with heart failure [191]. Also, response to hypoxia in adipocytes was related to gene promoter hypomethylation and up-regulation of proinflammatory cytokines [192]. Moreover, gestational intermittent hypoxia induced endothelial dysfunction, triggered pro-inflammatory gene expression, and caused epigenetic changes in adult male offspring to increase the risk of developing cardiometabolic disease [193].…”
Section: Climatementioning
confidence: 99%
“…A mechanistic role of inflammasome activation in determining aerobic capacity (measured by peak oxygen uptake) was suggested since the percentage of methylation of the ASC gene and plasma IL-1β levels correlated with aerobic capacity in stable outpatients with heart failure [191]. Also, response to hypoxia in adipocytes was related to gene promoter hypomethylation and up-regulation of proinflammatory cytokines [192]. Moreover, gestational intermittent hypoxia induced endothelial dysfunction, triggered pro-inflammatory gene expression, and caused epigenetic changes in adult male offspring to increase the risk of developing cardiometabolic disease [193].…”
Section: Climatementioning
confidence: 99%
“…The current study's findings indicate a direct association between VAT hypoxia and elevated TET1 protein and adipokine hypomethylation levels, implying that TET1 plays a role in the regulation of hypoxia-induced inflammation. This role was demonstrated mechanistically in our prior investigations, which showed an increase in HIF1α and TET1 protein levels and decreased global and gene-specific DNA methylation in adipocytes cultured under hypoxic conditions [16]. Together, our previous mechanistic findings in adipocytes along with the current correlation observed between HIF1α and TET1 in the adipose tissue suggest that obesity-related production of inflammatory cytokines could be mediated by an epigenetic process that is sensitive to changes in the adipose tissue microenvironment, specifically oxygen levels.…”
Section: Discussionmentioning
confidence: 55%
“…The role of TET1 has been recently explored in cancer and developmental diseases; however, there is an apparent lack in studying this mechanism in the context of obesity and vascular dysfunction [15]. We previously reported on the role of the HIF1α-inducible TET1 enzyme in causing hypomethylation and inducing mRNA expression of several adipokines in cultured adipocytes [16]. The current study will test this concept in adipose tissue samples obtained from obese and non-obese subjects.…”
Section: Introductionmentioning
confidence: 91%
“…When specifically looking for effects of Tet1, we found that the activities of Myc, Rest and Rreb1 were consistently reduced when Tet1 was lost in AT2 cells regardless of HDM status (Figure 7C). Hif1α, whose expression is regulated by Tet1 77 and may also regulate Tet1 expression 78 , showed reduced activity in KO-Saline (Figure 7D). Increased Foxa1 activity was only observed in KO-HDM compared to WT-HDM (Figure 7E).…”
Section: Resultsmentioning
confidence: 99%